Sublethal effects of triclosan and triclocarban at environmental concentrations in silver catfish (Rhamdia quelen) embryos - Gomes, Monike Felipe; de Carvalho Soares de Paula, Vinícius; Rocha Martins, Lucia Regina; Esquivel Garcia, Juan Ramon; Yamamoto, Flávia Yoshie [UNESP]; Martins de Freitas, Adriane (Elsevier, 2021)
Although banished in some countries, triclosan (TCS) and triclocarban (TCC) have been detected in surface waters in concentrations ranging from ng L−1 to μg L−1 and have shown to affect non-target organisms posing risk to aquatic ecosystems. However, the majority of the studies consider higher levels of these chemicals and single exposure effects to investigate their potential risks, rather than using environmentally relevant concentrations and their binary mixture. In this study, the toxicity of TCS and TCC, and their binary mixture was assessed in catfish embryos (Rhamdia quelen, a south American native species) exposed to environmental concentrations during 96 h. Organisms were evaluated through the endpoints of developmental abnormalities (spine, fin, facial/cranial and thorax), biochemical biomarkers related to oxidative stress responses: catalase (CAT), superoxide dismutase (SOD), glutathione-S-transferase (GST) activities, protein carbonylation (PCO) and neurotoxicity by acetylcholinesterase activity (AChE). The data showed that TCS caused fin abnormalities, decrease of SOD activity and increase of AChE activity in the catfish embryos of 96hpf. On the other hand, TCC and the binary mixture showed a higher abnormality index for the 96hpf embryos, and an induction of CAT and GST activities for the mixture treatment. The results obtained were able to show potential, but not severe, toxicity of TCS and TCC even in low concentrations and a short period of exposure. The relevance of studies approaching real scenarios of exposure should be reinforced, considering environmental concentrations of chemicals, interactions of contaminants in complex mixtures and the use of a native species such as R. quelen exposed during initial stages of development.
Keywords: Antimicrobials environmental effects; Biochemical biomarkers; Embryo fish toxicity; Mixture assessment; Oxidative stress